KELEMBAGAAN PENGELOLAAN MANGROVE BERBASIS MASYARAKAT DI KESATUAN PENGELOLAAN HUTAN MODEL WILAYAH III PROVINSI ACEH - Ok Hasnanda; Bramasto Nugroho; Hariadi Kartodihardjo; Nyoto x Nyoto Santoso (Jurnal Belantara, 2021)
Institutional community-based mangrove management as an alternative to sustainable management of mangrove forests. This study aims to analyze which factors from the institution most play a role in guiding the community in managing mangrove forest resources in relation to forest management units (FMU). Primary data were collected through interviews conducted semi-structured to 26 respondents selected by the purposive sampling method. The snowball method is used to capture information from key figures. Deepening is considered complete if information saturation has occurred which is marked by repetition of the same information. While secondary data, obtained from various libraries. Of the three models of mangrove management institutions, namely the community institution of Pusong Kapal Village (PKV), the community institution of Pusong Telaga Tujoh Village (PTTV), and the Community Forestry (CF-BM) Bina Mufakat institution where the analysis shows that the community institutions of Pusong Kapal Village (PKV) are more flexible as an alternative form of community-based mangrove management institutions, because this institution is able to adapt to the changing social and environmental conditions that continue to occur, the collaboration of management with the government, and the recognition of community rights in the use of mangrove forests. FMU as the management authority at the site level has guaranteed the upholding of the rights of the PKV community as the manager of mangrove forests so that the bundle of rights and incentives obtained in the management of mangrove resources by PKV communities becomes strong.